Optimal Stiffness Design to Limit Static and Dynamic Wind Responses of Tall Steel Buildings - Chan, Chun-Man (Engineering Journal, 1998)
With the continuing trend of constructing taller and slender buildings with higher strength materials and lighter structural systems, modern tall steel buildings are wind sensitive structures that are prone to serviceability problems. Two important serviceability limit states for tall building design are lateral deformations and motion perceptions under wind loads. Excessive lateral deformations have been found to cause windows to rack, non-structural partitions to crack and cladding to collapse. Exorbitant oscillations induced by turbulent wind have been known to cause occupant discomfort and even shatter windows.1,2 The functions of tall buildings may be disrupted due to inadequate design for serviceability. Indeed, the design of tall slender buildings is generally governed by serviceability stiffness criteria rather than by ultimate strength safety requirements. An automatic resizing technique for the optimal stiffness design of tall steel building frameworks is presented in this paper.